Withaferin A: a potential therapeutic agent against COVID-19 infection - Alex R. Straughn; Sham S. Kakar (BMC, 2020)
Abstract The outbreak and continued spread of the novel coronavirus disease 2019 (COVID-19) is a preeminent global health threat that has resulted in the infection of over 11.5 million people worldwide. In addition, the pandemic has claimed the lives of over 530,000 people worldwide. Age and the presence of underlying comorbid conditions have been found to be key determinants of patient mortality. One such comorbidity is the presence of an oncological malignancy, with cancer patients exhibiting an approximate two-fold increase in mortality rate. Due to a lack of data, no consensus has been reached about the best practices for the diagnosis and treatment of cancer patients. Interestingly, two independent research groups have discovered that Withaferin A (WFA), a steroidal lactone with anti-inflammatory and anti-tumorigenic properties, may bind to the viral spike (S-) protein of SARS-CoV-2. Further, preliminary data from our research group has demonstrated that WFA does not alter expression of ACE2 in the lungs of tumor-bearing female mice. Downregulation of ACE2 has recently been demonstrated to increase the severity of COVID-19. Therefore, WFA demonstrates real potential as a therapeutic agent to treat or prevent the spread of COVID-19 due to the reported interference in viral S-protein to host receptor binding and its lack of effect on ACE2 expression in the lungs.